Development and Validation of a Fall Prevention Knowledge Test. Issue 1 (9th October 2018) - Dykes, Patricia C.; Bogaisky, Michael; Carter, Eileen J.; Duckworth, Megan; Hurley, Ann C.; Jackson, Emily M.; Khasnabish, Srijesa; Lindros, Mary Ellen; Lipsitz, Stuart R.; Scanlan, Maureen; Yu, Shao P.; Bates, David W.; et al.
Abstract : Falls are a serious, persistent problem in hospitals. Ensuring that all hospital staff have adequate knowledge of how to prevent falls is the first step in prevention. We identified validated fall prevention knowledge tests (FPKTs) and planned to conduct a systematic literature review. When the review identified a lack of FPKTs, we developed and evaluated a FPKT, confirmed its conceptual framework, identified the content domain, drafted test items, devised the format, selected items for empirical examination, and conducted a psychometric evaluation. We randomly divided a 209‐subject data set into test and validation samples to make item reduction decisions and examine reliability and validity. The typical respondent was a white, 42‐year old female nurse with a bachelor's degree and 7 years' experience. Subjects were confident in their ability to prevent falls, rating themselves an 8 on a self‐efficacy scale of 1 (not at all) to 10 (very). The 11‐item FPKT scale (range 0–11) attained a tetrachoric coefficient of 0.73, confirming initial reliability. FPKT mean scores obtained before and after fall prevention education improved from 5.1 ± 1.8 to 6.6 ± 1.7. Statistically significant differences (paired t‐test = 12.4, p < .001) confirmed validity. A robust way to assess nurses' knowledge of fall prevention is needed to inform effective educational programs. Addressing gaps in validated FPKTs provides an opportunity to inform and evaluate effective fall prevention programs.J Am Geriatr Soc 67:133–138, 2019.